Character Building in Elementary Schools: A Study of Parental Involvement in Character Education - Muhammad Rifki Fatahillah; Jasiah; Santiani (al-Afkar, Journal For Islamic Studies, 2025)
This study examines the impact of parental involvement on character development in students at SDN 1 Basungkai. The aim of this research is to understand the contribution of parental involvement in fostering discipline, responsibility, and moral values among students, while also addressing the lack of research on the structural role of parents in character education. A qualitative descriptive approach was used, with data collection through interviews and observations to explore the interactions between parents, teachers, and students. The findings indicate that parental involvement has a positive influence on students' character development. However, informal forms of involvement, such as brief visits to the school and casual discussions with teachers, have limited long-term effects. Barriers such as work commitments and complex family situations also restrict the consistency of parental involvement. Nevertheless, this study highlights that structured collaboration between parents and schools through regular communication can enhance the effectiveness of character formation in children. The limitation of this study lies in its qualitative data from a single school, which affects the generalizability of the results. Future research is recommended to incorporate quantitative analysis in various school settings to strengthen and broaden these findings